Altruism as a buffer for antisocial behavior for African American adolescents exposed to community violence. Issue 2 (24th November 2017) - Rious, Jennifer Bryant; Cunningham, Michael
Abstract: Altruistic prosocial behavior during adolescence is consistently associated with a myriad of positive outcomes including fewer risk‐taking behaviors and greater positive affect. Although limited, some literature suggests altruism may be an important protective factor in attenuating the effects of stressful life events such as exposure to community violence. Unfortunately, work examining altruism in African American adolescents is quite limited. The study examined the moderating role of altruism on relationships between exposure to violence and antisocial behavior in a sample of African American adolescents (136 females, 71 males). Participant's age ranged from 13 to 18. Results indicated that boys and girls engaged in similar levels of altruistic behaviors, but these behaviors were especially important in moderating the effects of community violence on antisocial behaviors for boys. The findings suggest that encouraging altruistic behaviors in boys may be critical in improving outcomes for adolescent males developing in violent ecologies.